Rapid, regioselective deuteration of dimethyl-2, 2′-bipyridines via microwave-assistance. Issue 4 (8th December 2014) - Neranon, Kitjanit; Ramström, Olof
Abstract : Isotopically pure [D6 ]-dimethyl-2, 2′-bipyridine derivatives were selectively and rapidly formed using microwave-assisted regioselective deuteration of the methyl moieties of the parent bipyridine in a deuterium oxide solution. Abstract : Isotopically pure [D6 ]-dimethyl-2, 2′-bipyridine derivatives were selectively and rapidly formed using microwave-assisted regioselective deuteration of the methyl moieties of the parent bipyridine in a deuterium oxide solution. For instance, [D6 ]-4, 4′-dimethyl-2, 2′-bipyridine was formed in quantitative yield within 15 minutes, in a simple and convenient process.